2011
DOI: 10.1128/aac.01420-10
|View full text |Cite
|
Sign up to set email alerts
|

Double-Carbapenem Therapy for Carbapenemase-Producing Klebsiella pneumoniae

Abstract: The limited treatment options available for carbapenemase-producing Klebsiella pneumoniae (KPC) have made it a formidable pathogen. Previously we have shown the enhanced activity of pharmacodynamically optimized doripenem against KPC. Capitalizing on KPC's increased affinity for ertapenem, we evaluated the efficacy of a combination of ertapenem and doripenem in both an in vitro chemostat and an in vivo murine thigh infection model. Overall, the combination of doripenem plus ertapenem demonstrated enhanced effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
136
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 11 publications
4
136
1
5
Order By: Relevance
“…Two examples are avibactam, 31 recently FDA approved, and RPX7009, currently in stage III clinical trials. 32 Modulation of carbapenem susceptibility in CRE strains through use of double carbapenem therapy or tigecycline-carbapenem combination has also been suggested in human case reports, 33,34 animal models, and/or in vitro studies. 35 However, it could be imagined that there are many other classes of compounds that might restore carbapenem efficacy through effects on antimicrobial transport, cell wall dynamics, or currently unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Two examples are avibactam, 31 recently FDA approved, and RPX7009, currently in stage III clinical trials. 32 Modulation of carbapenem susceptibility in CRE strains through use of double carbapenem therapy or tigecycline-carbapenem combination has also been suggested in human case reports, 33,34 animal models, and/or in vitro studies. 35 However, it could be imagined that there are many other classes of compounds that might restore carbapenem efficacy through effects on antimicrobial transport, cell wall dynamics, or currently unknown mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…В эксперимен-тальной работе in vitro и в опыте на мышах была показана эффективность подобной комбинации [26]. Теоретическое обоснование такой схемы лечения заключается в следующем: эртапенем легче, чем дори-пенем гидролизуется карбапенемазами энтеробак-терий.…”
Section: карбапенемыunclassified
“…80 Others have found that various combinations of rifampin, β−lactams, aminoglycosides, quinolones, colistin/polymyxin B, fosfomycin or other agents are synergistic in vitro, or in animal models, against MDR Pseudomonas or Acinetobacter spp. 2,31,81,82 Many authors argue that rifampin should be considered for addition to other active antibiotics in the treatment of uncontrolled infection due to MDR bacteria, 31,55,78,83-85 though there is little evidence of why rifampicin should improve outcome and no randomized trials to show that it does improve these outcomes.…”
Section: Combination Therapy In Infections Due To Resistant Gram-negamentioning
confidence: 99%